Phytomedicinal Investigation from Six Mangrove Tree Species, North Sumatra, Indonesia (Investigasi Fitomedisinal Enam Spesies Mangrove, Sumatera Utara, Indonesia) - Mohammad Basyuni; Lollie A.P. Putri; Hirosuke Oku (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2013)
Manmgrove adalah tanaman yang toleran terhadap garam dan dikenal kaya sebagai sumber metabolit sekunder dengan potensi bahan obat alami seperti triterpenoida, alkaloida dan fitosterol. Zat kimia ini merupakan senyawa aktif untuk pengembangan agen bioaktif baru. Investigasi fitomedicin terhadap daun dan akar dari enam spesies mangrove di Sumatera Utara, Indonesia, yaitu Acanthus ilicifolius, Bruguiera parviflora, Ceriops tagal, Rhizophora apiculata, Sonneratia caseolaris dan Xylocarpus granatum dianalisis untuk karakterisasi profil kimianya. Identifikasi struktur fitokimia diverifikasi dengan perbandingan waktu retensi pada kolom GC dengan standar otentik dan interpretasi spektrum GC-MS. Skrining fitokimia menghasilkan pentasiklik triterpenoida dari golongan lupane, oleanane, ursane, kolesterol, fitol, squalene dan fitosterol. Triterpenoida dan fitosterol merupakan proporsi terbesar dari senyawa yang diisolasi. Komponen triterpenoida dan fitosterol masing-masing terdiri 7 dan 4 senyawa. Komponen utama dari triterpenoida adalah lupeol, a-amyrin, b-amyrin dan taraxerol. Fitosterol utama terdiri dari b-sitosterol, campesterol dan stigmasterol. Data ini dapat berkontribusi sebagai sumber bahan baku untuk pengembangan konstituen fitomedicin dan agrokimia dari tanaman mangrove Kata kunci: bioaktif, b-sitosterol, lupeol, mangrove, fitokimia, fitomedicin, fitosterol, triterpenoid Abstract Mangroves are salt tolerant plant and rich sources of secondary metabolites with potential medicinal value such as triterpenoids, alkaloids and phytosterols. These chemicals are promising active compounds for the development of novel bioactive agents. Phytomedicinal investigation of the fresh leaves and roots from six mangrove species, namely Acanthus ilicifolius, Bruguiera parviflora, Ceriops tagal, Rhizophora apiculata, Sonneratia caseolaris and Xylocarpus granatum from North Sumatra, Indonesia were analyzed to characterize their chemical profile. Identifications of the phytochemical structures were verified by comparison of their retention time on the GC column with those of authentic standards and on the interpretation of GC-MS spectra. Phytochemical screening yielded pentacyclic triterpenoids of lupane, oleanane and ursane group, cholesterol, phytol, squalene and phytosterols. Triterpenoids and phytosterols comprised the major proportion of compounds isolated. The triterpenoids and phytosterols consisted of 7 and 4 compounds, respectively. The major components of triterpenoids were lupeol, a-amyrin, b-amyrin and taraxerol. The main phytosterols consist of b-sitosterol, campesterol and stigmasterol. These data are likely to contributing a raw material source for development of phytomedicinal and agrochemical constituents from mangroves. Keywords : bioactive compound, b-sitosterol, lupeol, mangrove, phytochemical, phytomedicinal, phytosterol, triterpenoid